Safety and efficacy of regional citrate anticoagulation in continuous venovenous hemodialysis in the presence of liver failure: the Liver Citrate Anticoagulation Threshold (L-CAT) observational study. Issue 1 (December 2015) - Slowinski, Torsten; Morgera, Stanislao; Joannidis, Michael; Henneberg, Thomas; Stocker, Reto; Helset, Elin; Andersson, Kirsti; Wehner, Markus; Kozik-Jaromin, Justyna; Brett, Sarah; Hasslacher, Julia; Stover, John; et al.
Abstract Introduction Regional citrate anticoagulation (RCA) for continuous renal replacement therapy is widely used in intensive care units (ICUs). However, concern exists about the safety of citrate in patients with liver failure (LF). The aim of this study was to evaluate safety and efficacy of RCA in ICU patients with varying degrees of impaired liver function. Methods In a multicenter, prospective, observational study, 133 patients who were treated with RCA and continuous venovenous hemodialysis (RCA-CVVHD) were included. Endpoints for safety were severe acidosis or alkalosis (pH ≤7.2 or ≥7.55, respectively) and severe hypo- or hypercalcemia (ionized calcium ≤0.9 or ≥1.5 mmol/L, respectively) of any cause. The endpoint for efficacy was filter lifetime. For analysis, patients were stratified into three predefined liver function or LF groups according to their baseline serum bilirubin level (normal liver function ≤2 mg/dl, mild LF >2 to ≤7 mg/dl, severe LF >7 mg/dl). Results We included 48 patients with normal liver function, 43 with mild LF, and 42 with severe LF. LF was predominantly due to ischemia (39 %) or multiple organ dysfunction syndrome (27 %). The frequency of safety endpoints in the three patient strata did not differ: severe alkalosis (normal liver function 2 %, mild LF 0 %, severe LF 5 %;p = 0.41), severe acidosis (normal liver function 13 %, mild LF 16 %, severe LF 14 %;p = 0.95), severe hypocalcemia (normal liver function 8 %, mild LF 14 %, severe LF 12 %;p = 0.70), and severe hypercalcemia (0 % in all strata). Only three patients showed signs of impaired citrate metabolism. Overall filter patency was 49 % at 72 h. After censoring for stop of the treatment due to non-clotting causes, estimated 72-h filter survival was 96 %. Conclusions RCA-CVVHD can be safely used in patients with LF. The technique yields excellent filter patency and thus can be recommended as first-line anticoagulation for the majority of ICU patients. Trial registration ISRCTN Registry identifier:ISRCTN92716512 . Date assigned: 4 December 2008.